Coming out soon trillion-color TV. - Guizzo, E.
While film used in cinema contains pigments that can create an infinitely large number of color variations, TV sets combine discrete amounts of red, green, and blue light to create a much more limited color range. To produce more colors, TV sets would have to combine purer, or more saturated, red, green, and blue by using narrowband light filters that select colors more precisely but diminish brightness at the same time. Genoa Color Technologies Ltd., an Isreali company, has developed the software and hardware necessary to close this gap and make TV images more cinemalike without the unwanted dimming side effect. The trick is to add extra primaries, the basic colors that, combined, form all others. By adding yellow and cyan to the standard red, green, and blue, a display that could normally generate about 16.7 million colors would now be able to show more than one trillion. In a demonstration showing the overall color improvement, Genoa's multiprimary system exhibited colors that current television sets cannot display.
Keywords: Genoa Color Technologies Ltd; Color conversion algorithm; Color variations; Colored TV sets; Dimming side effect; Imaging circuit; Narrowband light filters; Trillion-color TV